Green Early-Stage Investments in the EU Member States - Małgorzata RUTKOWSKA; Jolanta PAKULSKA (Communications of International Proceedings, 2020)
Nowadays, eco (green) investments have been recognized as a key element in the transformation from a brown to a green economy. Eco-investments can be applied to all sectors of the economy, and all its dimensions: social, economic, and ecologic; Eco-investments are the applicable result of sustainable development actions among European Union countries. This paper presents the role of eco-investments among the EU member states and statistical analysis. This study is based both on qualitative and quantitative research methods. Then, the eco-investments on the European Eco-Innovation Scoreboard tool have been also analyzed, and the results were also presented. Source material for the examination were secondary data. As a result of this research, the leading eco-innovators were identified among factors influencing this type of investment.
Keywords: Eco-innovation; green early-stage investments; Eco-IS.